Health information systems : concepts, methodologies, tools and applications - Rodrigues, Joel, 1972- (Hershey PA : Medical Information Science Reference, 2010)
'This reference set provides a complete understanding of the development of applications and concepts in clinical, patient, and hospital information systems'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Medical informatics; Information storage and retrieval systems -- Medical care; Information systems; Electronic Health Records; Medical Informatics -- methods